AB0166 The Levels of Soluble CD163 in Patients with Ankylosing Spondylitis. (10th June 2014) - Tošovský, M.; Bradna, P.; Andrýs, C.; Andrýsová, K.; Čermáková, E.; Soukup, T.; Kubínová, K.; Krejsek, J.
Abstract : Background: Innate immune cells play an important role in pathogenesis of spondylarthropathies (SpA) since the increased infiltration of macrophages, especially CD163+, has been proven in synovitis tissue in these patients. Objectives: To evaluate the levels of soluble CD163 (sCD163) in patients with ankylosing spondylitis in comparison with patients treated for degenerative spinal disease. Methods: Levels of sCD163 were measured by enzyme-linked immunosorbent assay in patients with established ankylosing spondylitis according to modified New York criteria (n=55) and were compared with control group - patients treated for degeneratve spinal disease (n=20). Furthermore, we compared the levels of sCD163 in patients with ankylosing spondylitis treated (n=21) and not treated (n=34) with tumor necrosis factor alpha inhibitors. Results: The levels of soluble CD163 were significantly increased in group of patients with ankylosing spondylitis as compared with the control group (mean ± SEM 1670, 8±91, 6 ng/ml vs. 1131, 5±80, 3 ng/ml, p= 0, 0013). No significant difference was found between levels of soluble CD163 in patients treated and not treated with tumor necrosis factor alpha inhibitors (mean ± SEM 1805, 2±184, 8 ng/ml vs. 1587, 8±94, 4 ng/ml respectively, p =0, 52). Conclusions: Our finding shows, that CD163+ cells may play role in pathogenesis of spondylarthorpathies, particularly ankylosing spondylitis, and soluble CD163 may be applicable biomarker in this disorder. Acknowledgements: Supported by MH CZ –DRO (UHHK, 00179906) Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4464